A COMPREHENSIVE STUDY ON THE MICROSTRUCTURE AND OPTICAL PROPERTIES OF Fe3O4 NANOPARTICLES BY VARIATION OF TEMPERATURE AND NaOH CONCENTRATION - I Putu Tedy Indrayana (Prodi Fisika FST UNJA, 2019)
This work was aimed at optimizing the microstructure and optical properties of Fe3O4 by variation of synthesis temperature and NaOH concentration. The nanoparticles have been synthesized from iron sand by using the coprecipitation method. The temperature was varied of 60oC, 80oC, and 100oC, while NaOH concentration was 3 molar, 5 molar, and 7 molars. The microstructural parameters were characterized by using X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) techniques. The optical properties were characterized by using Fourier Transform Infrared Spectroscopy (FTIR) and UV-Vis Spectroscopy, consecutively. The results showed that the crystallite size of Fe3O4 increase with an increase of synthesis temperature due to higher thermal energy driving the nucleation process. The crystallite sizes are in the range of 3.77 nm – 20.37 nm. Increasing NaOH concentration also affected the increase in crystallite sizes. On the other hand, an excess of NaOH concentration influences the formation of smaller crystallite sizes of Fe3O4 with smaller crystal density and larger microstrain. The existence of Fe2+-O and Fe3+-O vibration in FTIR spectra confirmed the formation of Fe3O4 nanoparticles. The direct and indirect optical gap energies of Fe3O4 were in the range of 3.15 eV – 3.39 eV and 2.39 eV – 2.91eV. The synthesis temperature and NaOH concentration have a significant role in controlling the properties of Fe3O4.